Morphological characterization of some Calamus species of north-east India - Sarmah, P.=700 1 Kanta, Barua,P.
(En, Fr, Es)
ilus., 15 ref.
Keywords: CALAMUS (PALMAE); JUNCOS Y RATAN; ANATOMIA DE LA PLANTA; VARIACION GENETICA; INDIA